2020
DOI: 10.1007/s13593-020-00649-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of N-P-K demand and uptake in cassava

Abstract: Fertilizers are required to improve productivity of cassava and meet the increasing demand for cassava as food, feed, or raw material for processing industries. Our objective was to develop nutrition indices for N, P, and K to provide quantitative insight in the dynamics of nutrient demand and uptake of cassava. On-farm experiments were conducted at six locations in Nigeria from 2016 to 2018, across the major cassava growing agro-ecologies of West Africa. Nitrogen, P, and K were applied at different rates. Upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
(60 reference statements)
3
18
0
Order By: Relevance
“…Gómez et al ( 2018 ) proved the existence of a “dilution phenomenon” for K in potato and constructed critical shoot dilution curves for K in potato (Suprema: K c = 6.58 W −0.135 ). Adiele et al ( 2021 ) constructed the critical plant and shoot K dilution curves in cassava (the whole plant: K c = 4.2DM −0.69 ; shoot: K c = 4.3DM −0.54 ) and proved that the dilution of K concentration in leaves was less than that in roots, which is consistent with our study. Generally, the K dilution of sweet potato is less than that of potato and cassava.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Gómez et al ( 2018 ) proved the existence of a “dilution phenomenon” for K in potato and constructed critical shoot dilution curves for K in potato (Suprema: K c = 6.58 W −0.135 ). Adiele et al ( 2021 ) constructed the critical plant and shoot K dilution curves in cassava (the whole plant: K c = 4.2DM −0.69 ; shoot: K c = 4.3DM −0.54 ) and proved that the dilution of K concentration in leaves was less than that in roots, which is consistent with our study. Generally, the K dilution of sweet potato is less than that of potato and cassava.…”
Section: Discussionsupporting
confidence: 91%
“…KNI leaf has better advantages to combine with remote sensing than KNI root for monitoring the yield of sweet potato quickly. Adiele et al ( 2021 ) showed that there was a linear relationship between relative biomass yield and KNI in cassava, and KNI explained 65–66% of the variation for the relative biomass for all treatments. Gómez et al ( 2018 ) developed a quadratic polynomial model between N nutrition index (NNI) and potato yield, and NNI explained 73% of the variability in relative yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the dynamics of nutrient requirements and the impact of uptake limitations of cassava during the growth cycle enables prediction of cassava yields under nutrient limited conditions and may provide insight into best management practices to improve nutrient use efficiency. The nutrient contents of organs of the cassava plant vary during the growth cycle, but concentrations in the leaves fluctuate within narrow ranges ( Cock and Connor, 2021 ; Adiele et al, 2021a ). Typically, plants dilute nutrients over time as carbon accumulates ( Lemaire, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of nutrient (N, P and K) demand and uptake patterns under deficient conditions in cassava ( Adiele et al, 2021a ) can be used to develop a crop simulation model. After testing, such a model may be used for many purposes, including to generate crop responses for series of years to characterize cassava growth and nutrient uptake, provide location-specific fertilizer recommendations, and to extrapolate from the studied area to other areas where less detailed information is available.…”
Section: Introductionmentioning
confidence: 99%